CONSTRUING IDEATIONAL MEANING IN ELECTRONICS DEVICESADVERTISEMENTS IN JAWA POS: A SYSTEMIC FUNCTIONAL LINGUISTICMULTIMODAL DISCOURSE ANALYSIS - Ningsih, Erna Fitria; Tallapessy, Albert; Setiarini, Riskia (Publika Budaya, 2014)
This research deals with multimodal discourse analysis. The data were collected from printed advertisements ofJawa Pos newspaper. Generic Structure Potential of printed advertisement (GSP) proposed by Cheong (2004)and Hallidays (1994) transitivity were applied. Cheongs framework is applied to reveal the elements of visualand linguistic elements, meanwhile Hallidays transitivity is used to know the processes. Thereby, this researchdiscovers the relationship between image and text in one context. The result shows that visual elements in theprinted advertisements are Lead, Emblem, and Display. Lead consists of Locus of Attention (LoA) andComplements to the Locus of Attention (Comp. LoA). Meanwhile, the linguistic elements are Announcement,Emblem, Enhancer, Tag, and Call-and-Visit Information. Finally, it is found that there is interconnectednessbetween the visual and linguistic elements in the printed advertisement. It causes high ContextualizationPropensity (CP), narrow Interpretative Space (IS), and also small Semantic Effervescence (SE).Keywords: Generic Structure Potential (GSP), Ideational Meaning, Multimodal Discourse, PrintedAdvertisement